Peer effects in parental leave decisions - Clara Welteke; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper analyzes to what extent parental leave decisions of mothers with young children depend on the decisions made by their coworkers. The identification of peer effects, which are defined as indirect effects of the behavior of a social reference group on individual outcomes, bears various challenges due to correlated characteristics within social groups and endogenous group membership. We overcome these challenges by exploiting quasi-random variation in the costs ofparental leave during a narrow window around a cutoff date, induced by a parental leave benefit reform in Germany. The reform encourages mothers to remain at home during the first year following childbirth. Administrative linked employer-employee panel data enable us to assign a peer group to all individuals who work in the same establishment and occupational group. While there is a growing literature on peer effects, few studies look at peer effects in the context ofparental leave decisions. We argue, however, that mothers with young children are particularly susceptible to peer behavior at the workplace due to preferences for conformity with peer group behavior as well as the career-related uncertainty that mothers face. Our results suggest that maternal decisions regarding the length of parental leave are significantly influenced by coworker decisions, in particular in situations with high uncertainty.
Keywords: C31; J22; D04; 330; peer effects; social interaction; labor supply; family policy